Numerical Simulation of Free Convection Heat Transfer of Ferrofluid in an Oval Shaped Closed Loop - Mehta, Jaswinder Singh; Kumar, Rajesh; Kumar, Harmesh; Garg, Harry (Asian Journal of Engineering and Applied Technology, 2018)
Free convective heat transfer capability of kerosene based ferrofluid flowing through an oval shaped two-dimensional closed loop has been investigated numerically. COMSOL Multi Physics, a standard CFD code has been applied for solving the governing equations. A constant magnetic field was applied using permanent magnet and time dependent numerical study has been conducted for laminar fluid flow and heat transfer. The fluid was found to flow under the effect of externally applied magnetic field and spatially varying temperature. Maximum velocity of 4.43 mm/s has been found under the influence of externally applied magnetic field generated by the permanent magnet and flow was observed to be continuous. Temperature and velocity plots have also been plotted reconfirming the candidature of ferrofluid as a coolant for heat transfer applications of mini/micro devices.